The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.31083/j.ejgo4205149
|View full text |Cite
|
Sign up to set email alerts
|

Is minimal invasive surgical treatment of ovarian cancer plus HIPEC a utopia? A review of the literature

Abstract: The purpose of this study is to evaluate the effectiveness and safety of Hyperthermic Intraperitoneal Chemotherapy (HIPEC) approached by minimally invasive surgical (MIS) techniques. We conducted a systematic review of the published relevant studies and evaluated a total of 403 patients, with a median age of 57 years old (20-69). The histology of the patients included 160 (39.7%) patients with pseudomyxoma peritonei, 43 (10.6%) with mesothelioma peritonei, 37 (9.2%) with epithelial ovarian cancer (EOC), 80 (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Analyzing a series of data studied by Arjona-Sanchez [68] the results showed that L-CRS + HIPEC is a safe and practical surgery for carefully chosen patients with modest peritoneal illness when conducted at specialized facilities. Psomiadou [69] also supported the use of minimally invasive surgery with HIPEC.…”
Section: Treatmentmentioning
confidence: 91%
“…Analyzing a series of data studied by Arjona-Sanchez [68] the results showed that L-CRS + HIPEC is a safe and practical surgery for carefully chosen patients with modest peritoneal illness when conducted at specialized facilities. Psomiadou [69] also supported the use of minimally invasive surgery with HIPEC.…”
Section: Treatmentmentioning
confidence: 91%